Antynomie ludzkiej kondycji w "Marchołcie" Jana Kasprowicza - Podstawka, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Marchołt occupies an individual position in the literary output of Jan Kasprowicz. This drama was created in stages during a couple of years’ time, being entirely published only in the year 1920; wholly absorbing the artist until the end of his life. The multidimensional issue layer of the work was subordinated to a dramatic convention of mystery and is formed in the style of a morality play, with typical for the end of the 19th and the beginning of the 20th centuries, syncretic treatment of medieval religious theatres. An intrinsic key to deciphering Marchołt is to treat it as a synthesis of outlook changes and of the poet’s dilemmas, as an attempt of holistic presentation of the antinomies prescribed to the human condition. Kasprowicz constantly wrestled with the mystery of human existence, with characters’ vocation and with their life tracks since birth until death, pinpointing human inborn creation towards good and people’s plunging into sin, the spiritual and corporeal nature, the desire for freedom and entangling in illusions of happiness. He did not manage, however, to fully realize his drama inspirations and theatrical ambitions, in a „tragico-comic mystery” about Marchołt stopping halfway, signaling the direction of trespassing pessimistic and decadent anthropology. The true reconciliation will take place only in the poetic Book of the Poor (Księga ubogich), finding its completion in My world (Mój świat). Since the creation of Marchołt model, he tightly clings to rationalism of the contemporary civilization, being unable to accept its finiteness, the poet evolves affirmation of life synchronizing with nature, reconciling with himself and God, finding the long-awaited harmony of the universe.